2016
DOI: 10.1103/physrevlett.117.096405
|View full text |Cite
|
Sign up to set email alerts
|

Fermionic Symmetry-Protected Topological Phase in a Two-Dimensional Hubbard Model

Abstract: We study the two-dimensional (2D) Hubbard model using exact diagonalization for spin-1/2 fermions on the triangular and honeycomb lattices decorated with a single hexagon per site. In certain parameter ranges, the Hubbard model maps to a quantum compass model on those lattices. On the triangular lattice, the compass model exhibits collinear stripe antiferromagnetism, implying d-density wave charge order in the original Hubbard model. On the honeycomb lattice, the compass model has a unique, quantum disordered … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…3(a), which are realized when the parameter λ = 2J/J τ varies from pure J τ limit to a dominant J regime. Stripy-quadrupole phase I at small λ is essentially the same state as found earlier in compass model [25,26]; note, however, that the spin pattern in our "anti-compass" τ model is rotated by 90 • , for the reasons discussed in Sec. III A.…”
Section: Triangular Latticesupporting
confidence: 83%
See 1 more Smart Citation
“…3(a), which are realized when the parameter λ = 2J/J τ varies from pure J τ limit to a dominant J regime. Stripy-quadrupole phase I at small λ is essentially the same state as found earlier in compass model [25,26]; note, however, that the spin pattern in our "anti-compass" τ model is rotated by 90 • , for the reasons discussed in Sec. III A.…”
Section: Triangular Latticesupporting
confidence: 83%
“…( 10) by τ ]. This point has to be kept in mind while comparing the present τ -model results with those in canonical compass model studies [23][24][25][26][27].…”
Section: Non-kramers Eg Doublet and Pseudospinsmentioning
confidence: 99%
“…However, the exact ground state is not known in this case and its nature is in fact not clear, as several past works came to inconsistent conclusions. One study found a Néel state [96], others suggested a stabilization of a dimer pattern [97], a superposition of dimer coverings [98], or a quantum spin liquid state [99]. With the link to the compass model, the apparent special role of the −J = K = Γ point marked by a competition of four long-range ordered phases in its vicinity is confirmed.…”
Section: A Compass Point In the Phase Diagrammentioning
confidence: 91%
“…The fact that ground states of many-body systems can be disordered have intrigued condensed-matter physicists. Although quantum effects are the cause of groundstate disorder in many systems (for example, helium under normal pressure [1] and certain spin systems [2][3][4][5]), classical systems can also have disordered ground states [6][7][8][9][10][11][12][13]. A ground state of a classical many-particle or spin system is simply a global minimum of the potential energy.…”
Section: Introductionmentioning
confidence: 99%